The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/jmv.28768
|View full text |Cite
|
Sign up to set email alerts
|

Combination of novel oncolytic herpesvirus with paclitaxel as an efficient strategy for breast cancer therapy

Abstract: Background: New strategies are needed to improve the treatment of patients with breast cancer (BC). Oncolytic virotherapy is a promising new tool for cancer treatment but still has a limited overall durable antitumor response. A novel replicable recombinant oncolytic herpes simplex virus type 1 called VG161 has been developed and has demonstrated antitumor effects in several cancers. Here, we explored the efficacy and the antitumor immune response of VG161 cotreatment with paclitaxel (PTX) which as a novel onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Theoretically, the combination of oncolytic viruses and PD-1/PD-L1 inhibitors can overcome these limitations by improving the tumor immune microenvironment. In preclinical studies, the novel oncolytic virus VG161, when used in combination with PD-1 monoclonal antibody, demonstrates significant synergistic effects in a mouse model of pancreatic cancer ( Deng et al, 2023 ; Shen et al, 2023 ). Single-cell sequencing and flow cytometry experiments have revealed that VG161 promotes the infiltration of CD8 + T cells and natural killer (NK) cells into the tumor, thereby altering the tumor’s immune microenvironment and providing a conducive setting for the subsequent use of PD-1 monoclonal antibody.…”
Section: The Combination Of Oncolytic Virotherapy and Immune Checkpoi...mentioning
confidence: 99%
“…Theoretically, the combination of oncolytic viruses and PD-1/PD-L1 inhibitors can overcome these limitations by improving the tumor immune microenvironment. In preclinical studies, the novel oncolytic virus VG161, when used in combination with PD-1 monoclonal antibody, demonstrates significant synergistic effects in a mouse model of pancreatic cancer ( Deng et al, 2023 ; Shen et al, 2023 ). Single-cell sequencing and flow cytometry experiments have revealed that VG161 promotes the infiltration of CD8 + T cells and natural killer (NK) cells into the tumor, thereby altering the tumor’s immune microenvironment and providing a conducive setting for the subsequent use of PD-1 monoclonal antibody.…”
Section: The Combination Of Oncolytic Virotherapy and Immune Checkpoi...mentioning
confidence: 99%